2008
DOI: 10.1161/circulationaha.107.697979
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Insulin-Potassium for Acute Myocardial Infarction

Abstract: T he "holy grail" in the field of cardioprotection is to develop pharmacological agents that can be administered as adjunctive treatment to reperfusion that will reduce myocardial infarct size and improve clinical outcomes. Numerous pharmacological agents and strategies have been studied over the years with variable results in both animal models and humans. Of drugs that have been studied, only a few have shown benefit in clinical trials. Aside from agents or devices than can restore and maintain reperfusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 68 publications
1
35
0
2
Order By: Relevance
“…Subsequently, in 1983, Apstein et al 13 showed that hyperglycemia and insulin increased glycolytic flux and prevented ischemic contracture in the acutely ischemic rabbit heart. In an influential meta-analysis, Kloner and Nesto 14 found that even delayed GIK reduced 30-day patient mortality by ≈18%. Stimulation of glucose oxidation in rodent hearts decreased infarct size.…”
mentioning
confidence: 99%
“…Subsequently, in 1983, Apstein et al 13 showed that hyperglycemia and insulin increased glycolytic flux and prevented ischemic contracture in the acutely ischemic rabbit heart. In an influential meta-analysis, Kloner and Nesto 14 found that even delayed GIK reduced 30-day patient mortality by ≈18%. Stimulation of glucose oxidation in rodent hearts decreased infarct size.…”
mentioning
confidence: 99%
“…The debate on GIK has been described in detail in the past and has raged for decades. 68 The Immediate Myocardial Metabolic Enhancement During Initial Assessment and Treatment in Emergency Care (IMMEDIATE) trial was recently published. 69 This large, randomized, placebo-controlled, doubleblind, multicenter trial tested the efficacy of administering a 12-hour infusion of GIK started in the out-of-hospital setting by paramedics in patients with high probability of acute coronary syndromes.…”
Section: Glucose-insulin-potassiummentioning
confidence: 99%
“…Modulacja metabolizmu poprzez podawanie glukozy, insuliny i potasu (GIK), niezależnie od obecności cukrzycy i stężenia glukozy w osoczu, opiera się na założeniu, że zwiększenie stężenia potasu wewnątrzkomórkowego stabilizuje kardiomiocyty i ułatwia transport glukozy do komórek [324]. Do innych potencjalnych korzyści należą zmniejszenie beta-oksydacji wolnych kwasów tłuszczo-wych, lepsze wykorzystanie glukozy w procesie produkcji energii i poprawa czynności śródbłonka i efektów fibrynolizy [301].…”
Section: S 359unclassified
“…Do innych potencjalnych korzyści należą zmniejszenie beta-oksydacji wolnych kwasów tłuszczo-wych, lepsze wykorzystanie glukozy w procesie produkcji energii i poprawa czynności śródbłonka i efektów fibrynolizy [301]. Jak wynika z pracy przeglądowej Kloner i Nesto [324], w badaniach RCT nie wykazano zmniejszenia śmiertelności ani chorobowości. Ten brak efektu może być spowodowany zwiększeniem stężenia glukozy w osoczu lub niekorzystnym wpływem obciążenia płynami spowodowanego wlewem GIK.…”
Section: S 359unclassified